Damage Detection in Different Types of 3D Asymmetric Buildings Using Vibration Characteristics - Yi Wang; Ziru Xiang; Zhenyuan Gu; Chenhui Zhu; Wangping Qian (Shock and Vibration)
This paper treats the vibration characteristics of three different types of asymmetric buildings and investigates the feasibility of applying an innovative vibration-based multicriteria approach-based damage index (MCA-DI) technique to detect the damage. This technique combines a modified form of the traditional modal strain energy method (MSEM) developed by decomposing the mode shapes into lateral and vertical components together with a modified form of the modal flexibility method to define a new damage indicator. Lastly, the dynamic behavior of three asymmetric building instances, including a 10-storey L-shaped structure, a 10-storey setback structure, and a 6-storey reinforced concrete structure with an unsymmetrical distribution of columns, was studied under five different damage scenarios. The results showed that despite different vibration characteristics of these three asymmetric buildings, the proposed method was able to accurately and effectively locate all damages and eliminate the confusion when more than one index is simultaneously used by using only the first a few modes.